A Review of Computer Vision-Based Monitoring Approaches for Construction Workers’ Work-Related Behaviors - Jiaqi Li; Qi Miao; Zheng Zou; Huaguo Gao; Lixiao Zhang; Zhaobo Li; Nan Wang (IEEE Access, 2024)
Construction workers’ behaviors directly affects labor productivity and their own safety, thereby influencing project quality. Recognizing and monitoring the construction-related behaviors is therefore crucial for high-quality management and orderly construction site operation. Recent strides in computer vision technology suggest its potential to replace traditional manual supervision approaches. This paper explores research on monitoring construction workers’ behaviors using computer vision. Through bibliometrics and content-based analysis, the authors present the latest research in this area from three perspectives: “Detection, Localization, and Tracking for Construction Workers,” “Recognition of Workers’ Construction Activities,” and “Occupational Health and Safety Behavior Monitoring.” In terms of the literature’s volume, there has been a notable increase in this field. Notably, the focus on safety-related literature is predominant, underscoring the concern for occupational health. Vision algorithms have witnessed an increase in the utilization of object detection. The ongoing and future research trajectory is anticipated to involve multi-algorithm integration and an emphasis on enhancing robustness. Then the authors summarize the review from engineering impact and technical suitability, and analyze the limitations of current research from the perspectives of technical approaches and application scenarios. Finally, it discusses future research directions in this field together with generative AI models. Furthermore, the authors hope this paper can serves as a valuable reference for both scholars and engineers.